Introduction of CME Credit System amongst Doctors of Bangladesh Armed Forces - Ahmed, Masud; Pasha, A K M Mustafa Kamal; Waheed, S M Shameem (Journal of Armed Forces Medical College, Bangladesh, 2024)
Abstract not available JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 1-5